(3GdeWdhH TQM GdebUhO aj Yde GdUQas - (3eLghds
(3ChdgG (B:s
(3HSe Gddg GdLGQ eY GdeLQhQ eJYdb HGdaYd GdebOQ Zfj Yf JbOjQg dTgQJg gh aj GdCUd Seh fbdJ MQcI GdhGh Edi Gdejes
(3BNQgG (B:s
(3deG PcQ hHYVgG dYdI CNQi hgj eG PcQ CfgG aj YhQ hGYJhQ hZjQgeG aQLY gPG GdcdGe efg Edi YhQ hGYJhQ hZjQ Pdcs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf(B: 2 / 1807s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3GdUQas